Effectiveness of Community-Based Screening for Early Detection of Hepatocellular Carcinoma in Hepatitis B and C Patients: A Clinical Study - Muhammad Tariq Hamayun Khan, Amna Ikram, Shahzada Amir Ahmed Babar, Bilal Masood, Amna Jahan, Abdul Wadood Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatocellular carcinoma (HCC) is a major cause of cancer-related deaths globally, particularly in hepatitis-endemic countries like Pakistan. Chronic hepatitis B (HBV) and hepatitis C (HCV) infections remain leading risk factors. Due to asymptomatic progression, diagnosis often occurs at advanced stages when treatment options are limited. Community-based screening may offer a viable solution for early detection. Objective: This clinical study aimed to assess the effectiveness of community-based screening in the early diagnosis of HCC among patients with chronic HBV and HCV, presenting to tertiary care hospitals in Lahore. Methods: A cross-sectional study was conducted from June 2023 to May 2024 at Sir Ganga Ram Hospital and the Services Institute of Medical Sciences. A total of 100 patients with chronic HBV or HCV were enrolled, identified either via community outreach screening or hospital referrals. Diagnostic evaluation included liver function tests, serum alpha-fetoprotein (AFP), abdominal ultrasonography, and confirmatory imaging (CT/MRI). Tumor staging was classified using the Barcelona Clinic Liver Cancer (BCLC) system. Results: Among the 100 patients, 65% were identified through community-based screening and 35% through hospital referrals. Early-stage HCC (BCLC 0/A) was detected in 64.6% of community-screened individuals versus 25.7% in the hospital group (p < 0.01). AFP levels were significantly lower in early-stage cases. Imaging confirmed HCC in 72% of patients, with the remaining 28% showing non-malignant liver conditions. Conclusion: Community-based screening is significantly associated with early detection of HCC in hepatitis B and C patients. Incorporating such outreach initiatives into national healthcare strategies can improve timely diagnosis, enable curative interventions, and reduce the burden on tertiary care facilities in resource-limited settings. Keywords: Hepatocellular carcinoma, Community screening, Hepatitis B, Hepatitis C, Early detection, AFP, BCLC staging, Pakistan